UJI AKTIVITAS HIPOLIPIDEMIK EKSTRAK ETANOL HERBA KROKOT (Portulaca oleracea L.) PADA TIKUS OBESITAS DENGAN PARAMETER TRIGLISERIDA - Rizqi Nur Azizah; Bayu Putra; Rafika Tobis (Fakultas Farmasi UMI, 2018)
Hypolipidemics a drug used to lower plasma lipid levels in the blood. This study aimed to examine the hypolipidemic activity of ethanol extract of purslane herb (Portulaca oleracea L.) against the triglyceride level reduction in obese mice. The purslane herb contains omega-3, flavonoids and hight ascorbic acid as a lowering of triglyceride levels in the blood. This study used 15 malerats divided into 5 groups. Group I (negative control) was given Na.CMC 1%, group II (positive control) was given Gemfibrozil, group III, IV, and V were given ethanol extract of purslane herb with dose of 100 mg/kgBW, 200mg/kgBW, and 300 mg/kgBW as therapy group. All the administration were done orally once a day for 16 days. The measurement of triglyceride level was performed on early triglycerides before induction, after induction and after therapy. Before therapy, the rats were given hight-calorie diet. The results showed that the ethanol extract of purslanes herb has activity as hypolipidemic in lowering trygliseride level in obese mice. From the statistic result of One-Way ANOVA followed by LSD test, it can be concluded that the ethanol extract of purslane herb of the dose 100 mg/kgBW provide the most effective hypolipidemic activity that triglyceride level is not significantly different from positive control group (p>0,05).